2017
DOI: 10.1111/php.12846
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Dark Toxicity of the Photosensitizer TMPyP in Bacteria

Abstract: Photodynamic inactivation of bacteria (PIB) is based on photosensitizers which absorb light and generate reactive oxygen species (ROS), killing cells via oxidation. PIB is evaluated by comparing viability with and without irradiation, where reduction of viability in the presence of the photosensitizer without irradiation is considered as dark toxicity. This effect is controversially discussed for photosensitizers like TMPyP (5,10,15,20-Tetrakis(1-methyl-4-pyridinio)porphyrin tetra(ptoluensulfonate). TMPyP show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…In this context, it is worth mentioning a recent report in which 5 μM of photosensitizer (TMPyP) was sufficient to produce aPDI using ambient lighting at a power density of 0.13 mW/cm 2 , within a 10-minute exposure time. 42…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is worth mentioning a recent report in which 5 μM of photosensitizer (TMPyP) was sufficient to produce aPDI using ambient lighting at a power density of 0.13 mW/cm 2 , within a 10-minute exposure time. 42…”
Section: Resultsmentioning
confidence: 99%
“…Some studies affirm that a pre-incubation period improves aPDT outcomes, and available data show periods on the order of minutes, mainly 5-15 min [12,124,125]. Dark toxicity depends on PS concentration and microorganisms experimental type (i.e., biofilms or planktonic cells) [122]. Note that a greater ratio of light/dark toxicity means a more advantageous PS [126].…”
Section: Incubation Periodmentioning
confidence: 97%
“…PSs' dark incubation period (IP), also called the pre-irradiation period, is an essential factor in promoting the contact between the microorganism cells and the PS. At present, aPDT assays must consider longer incubation times designated as dark control in order to recognize PS cytotoxicity in total absence of light [122]. The period between PS administration and shining the light named as pre-incubation time (PIT) for antimicrobial purposes should be small (few minutes) since the PS uptake by the bacteria is fast in contrast to eukaryotic cells (IP: 4-24 h) [123].…”
Section: Incubation Periodmentioning
confidence: 99%
“…It has been reported that PS can reach and destroy blood cells, even when not administered intravenously [17,18]. That, in combination with residual dark toxicity of photosensitizers [19] can be a source of serious off target effects. To overcome these problems, novel delivery strategies have been developed.…”
Section: Introductionmentioning
confidence: 99%